1978
DOI: 10.1021/ja00482a053
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous polypeptide formation from amino acyl adenylates in surfactant aggregates

Abstract: Communications to the Editor 4605 (5) U. Lundescher and R. Schwyzer, Helv. Chim. Aca, 54, 1637 (1971).(6) Some authors had supposed7 that the NH and CO of cystine itself were responsible for extending two chains in opposite directions via hydrogen bonding. Our results obtained with compound 111, however, show that idea to be an oversimplification. (7) L. F. Fieser, Red. Trav. Chim. fay-Bas, 69, 410(1950); J. A. Glasel. J. Am.Chem. Soc., 87, 5472 (1965).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

1978
1978
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 4 publications
1
15
0
2
Order By: Relevance
“…Second, the results of several research groups were particularly interesting and conclusive as they observed the formation of oligopeptides when amino acid esters [310][311][312][313] or aminoacyl adenylates [307,314] were treated with CO 2 or bicarbonate solutions. The first results in this direction were reported by Korshak et al [311] as early as 1954.…”
Section: Ncas and The Hypothesis Of Molecular Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the results of several research groups were particularly interesting and conclusive as they observed the formation of oligopeptides when amino acid esters [310][311][312][313] or aminoacyl adenylates [307,314] were treated with CO 2 or bicarbonate solutions. The first results in this direction were reported by Korshak et al [311] as early as 1954.…”
Section: Ncas and The Hypothesis Of Molecular Evolutionmentioning
confidence: 99%
“…[310] It is obvious that the bicarbonate-catalyzed polymerizations of aaminoacyl adenylates also involved the formation of NCAs. [313,314] Finally, polycondensation of a-amino acids in aqueous buffered solution should be mentioned. [304,310,315] Under conditions where glutamic acid yielded oligopeptides, the preformed dimer Glu-Glu did not polymerize.…”
Section: Ncas and The Hypothesis Of Molecular Evolutionmentioning
confidence: 99%
“…Mittlerweile gibt es jedoch drei Arbeitsrichtungen mit Ergebnissen, die einer Rolle der NCAs in der präbiotischen Evolution eine erhebliche Glaubwürdigkeit verleihen. Erstens beobachteten mehrere Forschergruppen, [304][305][306][307][308][309][310] [310][311][312][313] oder Aminoacyladenylate [307,314] mit CO 2 oder Hydrogencarbonatlösung behandelt wurden. Erste Ergebnisse in diese Richtung wurden von Korshak und Mitarbeitern schon im Jahre 1954 beschrieben.…”
Section: Ncas Und Die Hypothese Der Molekularen Evolutionunclassified
“…[310] Es ist dementsprechend naheliegend, dass auch die durch Hydrogencarbonat katalysierte Polymerisation von a-Aminoacyladenylaten über NCAs verläuft. [313,314] Schließlich sollen noch Polykondensationen von a-Aminosäuren in gepufferter wässriger Lösung erwähnt werden. [304,310,315] Unter Bedingungen, unter denen Glutaminsäure Oligopeptide lieferte, brachte das Dipeptid GluGlu keine höheren Oligomere hervor, sodass wiederum die intermediäre Polymerisation von NCAs zur Erklärung der Oligopeptide herangezogen wurde.…”
Section: Ncas Und Die Hypothese Der Molekularen Evolutionunclassified
“…This work has focussed on reactions involving hydrolysis, aminolysis and nucleophilic substitution reactions (Broxton and Lucas, 1994;Fendler and Fendler, 1975;Menger, 1991 ;Menger and Fei, 1994) and, more recently, on oxidation (Engbersen et al, 1990;Panigrahi and Mishra, 1993) and decarboxylation (Patel et al, 1994) reactions. We are aware of only one report of micellar catalysis of a polymerization reaction (Armstrong et al, 1978). In this paper we report the catalysis by cetyltrimethyl ammonium bromide (CTAB) micelles of the polymerization of activated, negatively-charged amino acids.…”
Section: Introductionmentioning
confidence: 99%